High-Pressure Gas Injection in Carbonate Reservoirs: A Laboratory Investigation of Oil Displacement - Abdeli, Dairabay; Dongsheng, Han; Dong, Liang; Nadirov, Kazim; Yskak, Ardak; Zhantasov, Manap; Baibotayeva, Saltanat (Engineering, Technology & Applied Science Research, 2026)
Oil recovery from carbonate reservoirs is often limited by their heterogeneous permeability and complex fracture networks. This study investigates high-pressure gas injection as a method of enhancing oil displacement and maintaining reservoir pressure. Laboratory experiments were conducted on oil-saturated carbonate cores and sand-packed analogs to simulate flow redistribution and near-wellbore pressure conditions. The results indicate that maintaining elevated pressure within the elastic deformation range of rock and fluids promotes uniform lateral and vertical displacement, reduces preferential flow through high-permeability zones, and mobilizes oil from small pores and capillaries. Nitrogen injection achieved 62–68% oil recovery, with efficiency increasing with pressure and exposure time. The recommended methods for improving gas distribution in heterogeneous reservoirs are the pre-injection of proppant into the near-wellbore zone and well water shutoff via perforation and injection of gel-forming nanofluids and microcement. The findings demonstrate the potential of high-pressure gas injection to enhance sweep efficiency, reduce water and gas breakthrough, and support effective reservoir management.